Geological evolution of the basement rocks in the east-central part of the Rondonia Tin Province, SW Amazonian craton, Brazil: U-Pb and Sm-Nd isotopic constraints - Payolla, B. L.; Bettencourt, J. S.; Kozuchi, M.; Leite, W. B.; Fetter, A. H.; Van Schmus, W. R. (Elsevier B.V., 2002)
On the basis of geologic, petrologic, and U-Pb geochronologic data the basement rocks in the east-central part of the Rondonia Tin Province (RTP, southwestern Amazonian craton) are grouped into five lithologic associations: (1) tonalitic gneiss (1.75 Ga); (2) enderbitic granulite (1.73 Ga); (3) paragneiss; (4) granitic and charnockitic augen gneisses (1.57-1.53 Ga); and (5) fine-grained granitic gneiss and charnockitic granulite (1.43-1.42 Ga). The first three are related to development of the Paleoproterozoic Rio Negro-Juruena Province and represent the oldest crust in the region. The tonalitic gneisses and enderbitic granulites show calc-alkaline affinities and Nd isotopic compositions (initial epsilon(Nd) = +0-1 to -1.5; T-DM of 2.2-2.1 Ga) that suggest a continental arc margin setting for the original magmas. The paragneisses yield T-DM values of 2.2-2.1 Ga suggesting that source material was primarily derived from the Ventuari-Tapajos and Rio Negro-Juruena crusts, but detrital zircon ages and an intrusive granitoid bracket deposition between 1.67 and 1.57 Ga. The granitic and charnockitic augen gneisses show predominantly A-type and within-plate granite affinities, but also some volcanic arc granite characteristics. The initial epsilon(Nd) values (+0.6 to +2.0) indicate mixing of magmas derived from depleted mantle and older crustal sources. These rocks are correlated to the 1.60-1.53 Ga Serra da Providencia intrusive suite that reflects inboard magmatism coeval with the Cachoeirinha orogen located to the southeast. The fine-grained granitic gneiss and charnockitic granulites represent the first record of widespread magmatism at 1.43-1.42 Ga in northern Rondonia. Their geochemical signatures and the slightly positive initial epsilon(Nd) values (+0.7 to +1.2) are very similar to those of the most evolved granites of the calc-alkaline Santa Helena batholith farther southeast. U-Pb monazite and Sm-Nd whole-rock-garnet ages demonstrate that a high-grade tectonometa-morphic episode occurred in this region at 1.33-1.30 Ga. This episode attained upper-amphibolite conditions and is interpreted as the peak of the Rondonian-San Ignacio orogeny. The U-Pb and Sm-Nd data presented here and data published on rapakivi granites elsewhere indicate that the east-central part of the RTP is a poly-orogenic region characterized by successive episodes of magmatism, metamorphism, and deformation between 1.75 and 0.97 Ga. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: Amazonian craton; Rondonia Tin Province; Mesoproterozoic; U-Pb geochronology; Sm-Nd isotopes